STANDARISASI RESEP KUE BONGKO DI NAGARI KOTO BARU KECAMATAN IV NAGARI KABUPATEN SIJUNJUNG - Annisa Faradilla Suci; Lucy Fridayati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to standardize bongko cake recipes in the new Nagari Koto, Sijunjung Regency. The research method uses a mixed method. Data collection and data analysis techniques use interview, observation and documentation methods for qualitative types and questionnaires for quantitative data. Based on the results of qualitative research, bongko cake recipes are taken from 10 recipes in Nagari Koto Baru. Of the 10 recipes, the author analyzed the bongko cake recipe and then converted the same recipe from 10 experts, tested the bongko cake recipe by 5 experts by providing the same number of ingredients, conducted bongko cake research with 5 panelists with organoleptic tests, got 1 best recipe from 4 recipes that have been tested, 1 recipe that will be made a standard recipe. So this bongko cake recipe is Mrs. Marias's converted recipe. Good quality bongko cake in terms of neat shape with an average value of 4.6. The color of the bongko cake is of good quality which can be seen from the color is quite green with an average value of 3.3, the color of the soup is quite light brown with an average value of 3, the color of the wrapper is quite yellowish green on the bongko cake wrapper with an average value of 3.3. The aroma of hump cake dough gets k